Liver Stiffness, Not Steatosis, Predicts Mortality in MASLD Patients: An NHANES Analysis - Yuting Huang; Yichen Wang; Yan Yan; Samuel O. Antwi; Dilhana S. Badurdeen; Liu Yang (Livers)
Background: Metabolic dysfunction-associated steatotic liver disease (MASLD) has surged as a major cause of liver transplants in the United States. Existing studies have presented conflicting findings regarding the association between liver characteristics (specifically steatosis and fibrosis) and mortality. This study investigates the relationship between the controlled attenuation parameter (CAP) and liver stiffness measurement (LSM) via vibration-controlled transient elastography (VCTE) and all-cause mortality in MASLD patients. Methods: Using the NHANES 2017-2018 database, 3821 individuals representing the United States population with MASLD underwent VCTE for liver stiffness measurement. Exclusion criteria were applied, eliminating ineligible cases, incomplete examinations, underage individuals, and those with hepatitis B or C, along with significant alcohol consumption history. Cox proportional hazard models assessed the hazard ratio (HR) for all-cause mortality in CAP and LSM. Cox regression analysis with interaction terms was employed for deeper exploration. Results: The study unveiled a strong, independent correlation between LSM and all-cause mortality. However, the CAP failed to demonstrate a significant association with mortality in both univariate and adjusted analyses, contrary to recent findings. The analysis underscores the importance of accurately measuring liver stiffness via VCTE in predicting adverse outcomes in MASLD patients, emphasizing the pivotal role of fibrosis in assessing mortality risk. Conclusion: This study reaffirms the robust link between liver fibrosis (measured through VCTE) and mortality among MASLD individuals. The absence of a significant association between steatosis (indicated by CAP) and mortality challenges recent research, urging further comprehensive investigations with larger cohorts to delineate steatosis’ precise impact on MASLD-related mortality.